A Comparative Analysis of Super-Enhancers and Broad H3K4me3 Domains in Pig, Human, and Mouse Tissues - Peng, Yanling; Kang, Huifang; Luo, Jing; Zhang, Yubo (Frontiers in Genetics, 2021)
Super-enhancers (SEs) and broad H3K4me3 domains (BDs) are crucial regulators in the control of tissue identity in human and mouse. However, their features in pig remain largely unknown. In this study, by integrative computational analyses of epigenomic and transcriptomic data, we have characterized SEs and BDs in six pig tissues and analyzed their conservation in comparison with human and mouse tissues. Similar to human and mouse, pig SEs and BDs display higher tissue-specificity than their typical counterparts. Genes proximal to SEs and BDs are associated with tissue identity in most tissues. About 55~182 SEs (5%~17% in total) and 99~309 BDs (8%~16% in total) across pig tissues are considered as functionally conserved elements because they have orthologous SEs and BDs in human and mouse. However, these elements do not necessarily exhibit sequence conservation. The functionally conserved SEs are correlated to tissue identity in majority pig tissues, while those conserved BDs are linked to tissue identity in a few tissues. Our study provides resources for future gene regulatory studies in pig. It highlights that SEs are more effective in defining tissue identity than BDs, which is contrasting to previous study. It also provides novel insights on understanding the sequence features of functionally conserved elements.